Negotiation Preparation: Formulating The Negotiation Concept (International Journal of Scientific Trends, 2026)
In contemporary international relations, the success of political negotiations depends directly on the quality of the concept developed during the pre-negotiation phase. This article aims to explore the theoretical methodology and practical mechanisms for formulating a negotiation concept within the framework of international conflict resolution. The study employs qualitative analysis, a systems approach, and comparative political analysis. The article scientifically substantiates a three-stage model for creating an interstate negotiation concept: diagnosing the latent interests of the parties, information-psychological mapping, and institutionalizing BATNA, ZOPA, and "red lines." The practical viability of the proposed theoretical model is demonstrated through an in-depth case study of the 2024 multilateral mediation negotiations on the Gaza Strip (Paris and Doha formats). The research findings indicate that in polarized and asymmetric conflicts, the preparatory concept must possess a highly flexible architecture that accounts for the domestic political constraints of the negotiating states (based on the Two-Level Games theory). This study serves as a crucial scientific and practical guide for international relations specialists, foreign policy analysts, and practicing diplomats in designing strategic negotiations.